Attention bias modification produces no changes to appearance-related bias, state or trait body dissatisfaction in nonclinical women. Issue 2 (5th November 2015) - Loughnan, Siobhan A; Mulgrew, Kate E; Lane, Ben R
The potential of attention bias modification to reduce appearance-related attentional biases and female body dissatisfaction has not been investigated. Immediate and short-term effects were therefore examined across attentional biases, state and trait body dissatisfaction in a randomised controlled trial consisting of 62 female participants aged 18–35 years. The results show no changes to attentional bias across either the experimental or control condition and no significant changes in body dissatisfaction immediately post-training or at 1–2 weeks follow-up. Single-session attention bias modification protocols may therefore not be sufficient in modifying appearance-based biases and associated disordered body schemas within a nonclinical sample.